8(7-z)=-7z

Simple and best practice solution for 8(7-z)=-7z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8(7-z)=-7z equation:



8(7-z)=-7z
We move all terms to the left:
8(7-z)-(-7z)=0
We add all the numbers together, and all the variables
8(-1z+7)-(-7z)=0
We multiply parentheses
-8z-(-7z)+56=0
We get rid of parentheses
-8z+7z+56=0
We add all the numbers together, and all the variables
-1z+56=0
We move all terms containing z to the left, all other terms to the right
-z=-56
z=-56/-1
z=+56

See similar equations:

| -1/5c-7=-3 | | 6x-15=5x+48 | | 1+10x+3=-16 | | 2d+8=6d | | 8n-6=6n | | -6w-+1=-11 | | 7v-2=7v-8-v | | n/7+2=-10 | | 2.7+6=u | | 3(2x+-3)=-2(x+4) | | 3p=-3+4p | | 2x+5x-3=5x-2 | | x=212=24 | | 5=3d−4 | | 6(8-1)=6x-1 | | 5x+5+5x+5=80 | | 3(2x+3)=-2(x+4) | | 2(x-1)+34=6x | | -10(8n+5)+12n=-254 | | x+49=4x+1 | | 12x+15=15x3 | | 2.5y+7=4.5y-1 | | -2xx-3=11 | | 4n=-6n-10 | | -8r=-9r-9 | | |−2y+5|=2|4y−1|. | | 5(6x)=10 | | 3x°=(12x-30)° | | 4.5x-6=0 | | t-4=0.6 | | x-8+5=4 | | -19m—4m+8m=-7 |

Equations solver categories